2022
DOI: 10.3390/ijerph19052634
|View full text |Cite
|
Sign up to set email alerts
|

Microalgal Cultures for the Bioremediation of Urban Wastewaters in the Presence of Siloxanes

Abstract: Microalgae are widely used in the bioremediation of wastewaters due to their efficient removal of pollutants such as nitrogen, phosphorus, and contaminants of emerging concern (CECs). Siloxanes are CECs that reach wastewater treatment plants (WWTPs), leading to the production of biogas enriched with these compounds, associated with the breakdown of cogeneration equipment. The biological removal of siloxanes from wastewaters could be a sustainable alternative to the costly existing technologies, but no investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 46 publications
2
6
0
Order By: Relevance
“…In addition, heavy metals and other harmful substances can be absorbed by microalgae through biosorption and bioaccumulation processes. Chlorella vulgaris was shown by Salgado et al [25] to efficiently remove nitrogen and phosphate from wastewater when employed in an AMBR. This study demonstrated the ability of AMBRs to eliminate nutrients by reporting a>90% reduction in total nitrogen and phosphate [25].…”
Section: Algae As a Promising Biological Resourcementioning
confidence: 99%
See 1 more Smart Citation
“…In addition, heavy metals and other harmful substances can be absorbed by microalgae through biosorption and bioaccumulation processes. Chlorella vulgaris was shown by Salgado et al [25] to efficiently remove nitrogen and phosphate from wastewater when employed in an AMBR. This study demonstrated the ability of AMBRs to eliminate nutrients by reporting a>90% reduction in total nitrogen and phosphate [25].…”
Section: Algae As a Promising Biological Resourcementioning
confidence: 99%
“…Chlorella vulgaris was shown by Salgado et al [25] to efficiently remove nitrogen and phosphate from wastewater when employed in an AMBR. This study demonstrated the ability of AMBRs to eliminate nutrients by reporting a>90% reduction in total nitrogen and phosphate [25]. The study by Leong and Chang [26] demonstrated that Chlorella and Scenedesmus, like microalgae, are capable of removing heavy metals such as Cd, Cr, and Pb from wastewater through bioaccumulation and biosorption processes.…”
Section: Algae As a Promising Biological Resourcementioning
confidence: 99%
“…The microalgae C. vulgaris CCAP 211/11B was acquired from the Culture Collection of Algae and Protozoa (CCAP, Oban, UK). The stock solutions were made in 100 mL Erlenmeyer flasks using the modified Organization for Economic Co-operation and Development (OECD) test medium described by Salgado et al [23]. The Erlenmeyer flasks were continuously exposed to light (light:dark ratio of 24:0) with 6.50 µmol m −2 s −1 of intensity and kept at room temperature.…”
Section: Microorganisms and Culture Mediummentioning
confidence: 99%
“…Even though several studies report the effective use of C. vulgaris for conventional pollutants removals, such as nitrogen and phosphorus [25,26], few are related to disinfection and ARGs reduction of abundance [4,20,24]. To the authors' knowledge, none has evaluated the removal of conventional pollutants and the reduction of pathogens proliferation and ARGs abundance in the same system.…”
Section: Introductionmentioning
confidence: 99%